Seeking hegemony : the very political construction of public policy concerning land in Uganda under the National Resistance Movement : Oscillating between change and inertia - (:unkn) unknown (My University, 2016)
Land tenure, defined as the set of relations among humans that determine their interaction with land, lies at the heart of power struggles, especially in agrarian societies. Governing land management through public policy means changing power relations between the state and the local institutions that exercise social control. Using Uganda under the regime of the National Resistance Movement (NRM) as its case study, this thesis in political science explores the manner a public policy concerning land is constructed through the interactions among various power structures. We are dealing here with the interactions among polity, politics and policy. Examined as a political activity, the construction of a public policy concerning land in African contexts goes beyond a matter of concern for the state alone. This activity is a source of political legitimacy for those actors participating in the process. Its instrumentalisation can lead to changes in power relations. This process starts with the construction of the problem and ends with the negotiation of a solution. This inductive research is based on qualitative research methods : participant observation, semi-structured interviews, analysis of grey literature and of archives. It is based on four years of field work in Uganda. This thesis innovates theoretically as it integrates the discursive and pragmatic approach of public policy to structuration theory. It ties this approach to the notion of « historicity of the imported state ». This theoretical framework allows us to study the ordering and disordering of society that are triggered by the formulation of problems and solutions. It provides a detailed empirical study of public policy concerning land in Uganda. This thesis contributes, more generally, to the study of democratisation in Africa, land tenure in Africa and public policy in African contexts.
Keywords: African Research